L'enseignement à distance dans l'enseignement supérieur - Yaroslav Opanasenko; Viktoriia Novikova
Distance learning has become one of the most popular educational trends of the 21st century, and the COVID-19 pandemic and war in Ukraine has only accelerated the process of its integration into the education sector. The purpose of our work is to study the influence of the online learning format on the adaptation and academic success of students, as well as to search for promising analogues.